HALAL VALUE CHAIN DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF PADA BISNIS KULINER - Nuratikah, Nuratikah; Wahyudin Abdullah, Muhammad; Awaluddin, Murtiadi; Nurjanah, Nurjanah (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
Many countries concentrate on the business of procuring halal products. The halalness of a product is indicated by the presence of a halal logo on the packaging. The halal logo can be used to indicate that a product meets the requirements set by sharia law so that it is suitable for consumption by Muslims, therefore implementing the halal value chain in the culinary business is very important. So, when a business wants to be superior to its competitors, a competitive strategy within the company is very necessary in achieving the goals of an organization or company in business competition, namely Competitive Advantage. Here it is interpreted that strategy is more about how to make plans, tactics, winning positions, patterns and perspectives that are created to be implemented over a long period of time, so that the end is how to win the market. The research method used in this research is a literature review of various studies that have been carried out by previous researchers. The data collection method used is secondary data obtained from journals, documentation books, scientific articles and other documents relevant to this research